Mapping the energy sector issues in the Philippines - Adoracion M. Navarro; Jethro El L. Camara (Philippine Institute for Development Studies (PIDS), 2023)
Given the frequent observation that the Philippine energy sector is complex, this study provides a structured review of issues in the sector. The structured review method is usually employed to systematically introduce readers to the complexities of a broad topic, such as the convolutions of a problem, the intricacies of a theme or sector, or the conjectures about a new trend or technology. The study starts with a discussion of the physical flows of energy via a Sankey diagram of energy flows in the Philippines, and then proceeds to describe the upstream oil, gas, and coal industry, the downstream oil industry, the renewable energy development industry, and the electric power industry. The discussion includes the market structure, regulatory framework, and issues in each industry. As the analysis shows, structuring the understanding of the energy sector by component industry is a useful approach to untangling the complexities of the sector. As part of the concluding remarks, the study claims that another useful approach is to look at problems in the energy sector as cross-cutting concerns or cutting across several industries, such as the energy affordability problem. All the issues identified in the study can be considered future research areas by public and private entities interested in Philippine energy sector research because all those issues are affecting the country's energy security. Nevertheless, what may be considered as priority future research areas at present are energy affordability concerns and issues that can be addressed by amending the EPIRA.
Keywords: 330; energy; upstream industry; downstream oil industry; renewable energy; electric power industry; energy security; energy affordability; clean energy transition